A Compound Curve Fit Analysis of FDI Flows in Selected Sectors in India - L. , Sujatha; kumar, Radhaganesh; J. , Anand (International Journal of Psychosocial Rehabilitation, 2020)
This paper attempts to analyze foreign direct investment flows in selected sectors. An analytical research is attempted to investigate the compound fit for the FDI flows in three selected sectors, such as the service, telecommunication, and drug and pharmaceutical industries, for the years 2005-15. Suitable suggestions are given based on flows in selected sectors.